Peningkatan Kemampuan Menulis dengan Menggunakan pendekatan keterampilan Proses untuk Siswa Sekolah Dasar - Rahayu, Sri; Rosdiana (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2022)
This study aims to improve the quality of learning. The quality of learning that is improved in this study includes the activities and learning outcomes of students. This research is Classroom Action Research (CAR) which is carried out in two cycles. The research subjects were fourth-grade students of SDIP Assunnah Tamalate Makassar in the 2020/2021 academic year. The data obtained in this study is quantitative. Data collection techniques used are test and non-test techniques. The research instruments used include Learning Implementation Plans (RPP), test instruments, and non-test instruments. The data analysis technique used is to calculate multiple-choice test scores, determine the class average, and the percentage of complete learning. The final score on the formative multiple-choice test is obtained by dividing the number of correct answers by the total number of items and then multiplying by one hundred. The percentage of student learning activities in the first cycle was 66.67% or 20 students were in a complete category and as many as 10 people or 33.33% were in the incomplete category. In cycle II, 100% or 30 students were in a complete category and nothing else or 0% were in the incomplete category. The results of the research activities above prove that the learning outcomes of Indonesian language learning materials for writing paragraphs in fourth-grade students of SDIP Assunnah, Makassar through the application of the process skills approach have increased. Researchers provide suggestions for improving the quality of learning. Suggestions given by researchers are intended for teachers and schools